Pembuatan Media Video Untuk Pembelajaran Jarak Jauh di SD Negeri Batursari 6 - Nizaruddin Nizaruddin; Sutrisno Sutrisno; Noora Qotrun Nada; Nurina Happy (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The teacher's ability to create media for distance learning must be improved. This service activity aims to provide training and assistance to teachers of SD Batursari 6 Mranggen District, Demak Regency, Central Java in making instructional videos. The software used was Google Photo, Wondershare Filmora, Thunkable, and PowerPoint 2020. The activity was carried out in a blended manner for four days of activity. The training is carried out using an andragogical approach, where training involves more demonstrations, questions and answers and practice as well as mentoring. The training material is presented with more practice than theory, with a ratio of 30% theory and 70% practice. The success of the training was demonstrated through the improvement of the participants’ abilities regarding the use of software to make learning videos. The ability in making media is shown from the learning media products that have been made by the teacher. All prtiipant responded positively to this activity.